Application of Biological Accounting for Wood Commodities at Perum Perhutani - Marota, Rochman; Lestari, Retno Martanti Endah; Johari, Razana Juhaida (Universitas Pendidikan Ganesha, 2024)
Wood commodities constitute the most significant income of Perum Perhutani; therefore, recording the value of inventory and sales must be done by applicable Financial Accounting Standards. This research aims to empirically prove the influence of disclosure, measurement, and disclosure dimensions on applying biological accounting for managing wood resources at Perum Perhutani. This research uses quantitative research methods with a case study approach. Data was obtained through interviews and focused group discussions with internal company parties regarding the application of biological accounting and analyzed using a structural equation model (SEM). The research results show that Perum Perhutani has made several efforts to apply biological accounting to manage wood resources. That is reflected in the implications of biological accounting policies that have been implemented well. The application of biological accounting at Perum Perhutani can help increase the efficiency of resource allocation, optimize the economic value of wood products, and support strategic decision-making that is oriented toward sustainability. From an environmental perspective, biological accounting provides advantages in identifying and reducing the negative impacts of timber forest exploitation activities.